CTLA‐4 and HLA‐DQ are key molecules in the regulation of mDC‐mediated cellular immunity by Tregs in severe aplastic anemia. Issue 10 (3rd July 2020) - Liu, Bingnan; Shao, Yuanyuan; Liang, Xiaowei; Lu, Dan; Yan, Li; Churov, Alexey; Fu, Rong
Abstract: Background: Regulatory T cells (Tregs) inhibit the activation of cluster of differentiation (CD) 4 +, CD8 + T cells and the antigen‐presenting process of antigen‐presenting cells, and may play an important role in acquired severe aplastic anemia (SAA). Methods: Flow cytometry was used to measure CD4 + CD25 + CD127 dim Tregs, cytotoxic T lymphocyte antigen 4 (CTLA‐4) expression on Tregs, and human leukocyte antigen (HLA)‐DQ expression on myeloid dendritic cells (mDCs). The correlations of CTLA‐4 and HLA‐DQ with immune status and clinical indicators and the changes in these indicators after immunosuppressive therapy (IST) were analyzed. Results: In SAA patients, the number of Tregs and their CTLA‐4 expression were low but recovered after IST; the HLA‐DQ expression on mDCs was high but decreased after IST. The CTLA‐4 expression on Tregs and the HLA‐DQ expression on mDCs showed a negative correlation. The CTLA‐4 on Tregs was positively but HLA‐DQ on mDCs negatively correlated with the number of Tregs, natural killer (NK) cell number, and CD4 + T/CD8 + T ratio. CTLA‐4 was positively but HLA‐DQ negatively correlated with the percentage of granulocytoid and erythroid cells in bone marrow, white blood cell count in PB, absolute neutrophil count in PB, and the percentage of reticulocytes in PB. Conclusions: CTLA‐4/HLA‐DQ may be key in the regulation of Tregs on mDCs in SAA patients. Our findings should be helpful for further investigation of the mechanism of immune pathogenesis in SAA patients. Studies on the regulators of Treg and CTLA‐4 activity will be valuable for SAA therapeutic target research and disease monitoring. Abstract : CTLA‐4 and HLA‐DQ regulate cellular immunity by Tregs and mDC in SAA. A, CD4 + CD125 + CD127 dim /PBL in the SAA, RSAA, and HC groups. B, CTLA‐4 + Treg/Treg in the SAA, RSAA, and HC groups. C, HLA‐DQ + mDC/mDC in the SAA, RSAA, and HC groups. D, Negative correlation between the CTLA‐4 expression on Tregs and the HLA‐DQ expression on mDCs in SAA patients. *** P < .001, ** P < .01, * P < .05. HC, healthy control (n = 24); RSAA, recovering severe aplastic anemia (n = 23); SAA, severe aplastic anemia (n = 21).